The Study of Good Manufacturing Practices (GMP) and Good Quality Wingko Based on SNI-01-4311-1996 - Heru Rudiyanto (Universitas Airlangga, 2016)
Abstract: Wingko is a special snack from Kecamatan Babat, Kabupaten Lamongan. One of home industries that produce Wingko in Babat City is UD. Bintang Jaya. The making process of Wingko is done traditionally, by using human power. It is really possible for microorganisms to contaminate and affect the quality of Wingko through this process. To raise the quality of food, food controlling is badly needed. Good Manufacturing Practices (GMP) is one of systems that describes the terms that have to be fulfi lled by home industries. The purpose of this research is to identify the production of wingko according to GMP perspective and the quality of Wingko based on SNI-01-4311-1996, and to make GMP plan for the home industries. This is an observational research. Based on the data, this research is observational descriptive, while according to the period of the research, this is a crossectional research. The sample for this research is Wingko, the owner and the employees whoever involve in the production. The variable in this research consists of staple, employees health, production tools, location and facilitations, E.coli and sweetener (saccharin and cyclamate), and last but not least the sensory aspects. The research shows the good categorized variables are: staple, production tools, health employees sensory aspects. Meanwhile the adequate categorized are: location and facilitations. The result of laboratory test over E.coli and sweetener, shows that these are qualifi ed based on SNI 01-4311-1996 about Wingko's grade standard. The variables that don't meet the qualifi cations of (GMP), are suggested to be improved to make better results and more qualified, while the qualifi ed variables based on GMP are expected to keep their good conditions.Keywords: Wingko, Food Grade Quality, GMP